Opportunities and Challenges for Islamic Education Teachers in Using Artificial Intelligence in Learning - Najah Baroud; Yoni Ardila; Fauzi Akmal; Rifdah Sabrina (International Islamic Studies Development and Research Center (IISDRC), 2025)
The phenomenon of using Artificial Intelligence in education has become common. Not only in terms of work, Artificial Intelligence can also be used in the world of Islamic Education. This shows that Artificial Intelligence can also help Islamic Education teachers in learning. This research aims to analysis the challenges and opportunities for Islamic Education teachers in using Artificial Intelligence in learning. The method used in the research is a qualitative method with data sources taken through interviews with forty informants consisting of Islamic Education teachers from elementary to high school level. The results of data analysis found that Artificial Intelligence is proven to provide opportunities and convenience for Islamic Education teachers in the learning process although there are also some challenges. Among the opportunities for Islamic education teachers in using Artificial Intelligence in learning are i) making it easier for teachers to access learning, ii) saving costs, iii) creating interesting and innovative learning media. However, the challenges in using Artificial Intelligence are i) unstable networks, ii) lack of teacher training in the use of artificial intelligence, iii) information obtained is less accurate, iv) lack of teacher privacy. This research can be used as a reading for Islamic religious education teachers in preparing themselves to become creative and professional teachers.